Estrogen and progesterone receptors immunolabeling in mammary solid carcinoma in an African Hedgehog (Atelerix albiventris) with concurrent uterine fibrosarcoma - Fernandes, Natália C. C. A.; Réssio, Rodrigo A.; Guerra, Juliana M.; Wasques, Danilo G.; Dagli, Maria Lucia Z. (Brazilian Journal of Veterinary Pathology, 2017)
The African Hedgehog (Atelerix albiventris) has gained popularity as a pet in several parts of the world. This is a report of a concomitant finding of spontaneous mammary and uterine tumors in an adult female African Hedgehog. The animal presented abdominal masses and died suddenly. Upon necropsy, not only the mammary tumor mass, but also a uterine neoplasm was found. Formalin fixed and paraffin embedded tissues were submitted for histopathological examination. The mammary tumor was diagnosed as a solid carcinoma, and the uterine tumor as fibrosarcoma. By immunohistochemistry, the mammary tumor showed positivity for pancytokeratins and estrogen and progesterone receptors, while the uterine neoplasm exhibited positivity for vimentin. There was high cross-immunoreactivity between anti-human antibodies. The positivity for hormonal receptors antigens may represent a relationship between estrogen and progesterone levels and the development of mammary tumors, as in other mammals.